REQUEST TYPES OF CHARACTERS’ UTTERANCES WITHIN “TO ALL THE BOYS: ALWAYS AND FOREVER” MOVIE - Fanny Virginia; Ambalegin Ambalegin (eScience Humanity Journal, 2022)
The purpose of this descriptive qualitative research was to reveal request types in movie characters’ utterances. 2021 American teen rom-com movie entitled “To All the Boys: Always and Forever” was used as the data source. All data of this research were obtained from the movie characters' request utterances. Observational method and note-taking technique were used to do the data collection. Data were analyzed by using a pragmatic identity method and pragmatic competence-in equalizing technique. In revealing the types, theory of request types discovered by Tsui (1989) was applied. For the research result, five request types were found and those types appeared in 62 data. Specifically, request for action had 23 data, offer and invitation showed eight data for each type, propose was found to have 12 data, and request for permission got 11 data. The result also revealed that request for action was the most commonly conveyed type. This is considering the characters conveyed lots of request utterances to influence the hearers to get requested actions done for the speakers’ benefits.